Uganda’s pork value chain benefits from a decade of research and action - Lukuyu, Ben A.; Ouma, Emily A. (International Livestock Research Institute, 2022)
CGIAR and its partners have been working with Uganda’s pork value-chain actors for a decade (2012–22) to help them to meet the rising demand for pork products. CGIAR research identified seven major constraints to Uganda’s pig production: genetic quality of breeding pigs, feed availability and quality, pig health and biosecurity, access to advisory services, environmental sustainability, market systems and access, and links and collaboration along the pork value chain. Successive projects have developed strong partnerships and collaboration to co-design, test, pilot and deliver integrated intervention packages to pork value-chain actors to increase their productivity and productivity. Now, Uganda’s pork production is more visible on national and regional agendas and is a higher priority for government policy and action. We need to synthesize, further test and invest in scaling up packages of interventions to ensure Uganda’s pork value chain continues to meet demand.